(untitled) (Research, Society and Development, 2020)
Objective: Obtain a historical analysis of data related to hospitalizations, total amount spent and days dedicated to diabetes mellitus by a unit of the Brazilian Federation of Ancients over the past 10 years. Methodology: it is an ecological, retrospective study and time series with censorial data from the Health Unic System Department of Informatics. Results: the peak of hospitalizations in Brazil between 2009 and 2019 occurred in the year 2011 and the year with the most expenses with hospitalizations in 2019. The Northeast stood out together with the Southeast leading the variables in all age groups. For all age groups and all variables, the Middle West has the lowest number of hospitalizations among all Brazilian regions. Conclusion: the number of hospitalizations, hospitalization days and the total amount spent by Diabetes Mellitus in the last 10 years for the elderly shows a crucial characteristic, except in 2012 and 2016. The southeast leads the analysis majority, followed by the noreste, the sur, North and, finally, the Middle West.